Bisphenol A induces COX-2 through the mitogen-activated protein kinase pathway and is associated with levels of inflammation-related markers in elderly populations - Song, Heewon; Park, Joonwoo; Bui, Phuong T.C.; Choi, KeunOh; Gye, Myung Chan; Hong, Yun-Chul; Kim, Jin Hee; Lee, Young Joo (Environmental research, 2017)
Bisphenol A (BPA) is a well-known endocrine-disrupting chemical, and it is one of the highest volume chemicals produced worldwide. Even though several in vivo and in vitro studies showed positive associations of BPA exposure with pro-inflammatory cytokines such as tumor necrosis factor-α and interleukin (IL)-6, the mechanism by which BPA induces inflammation is unclear. We investigated the mechanism by which BPA induces inflammation (expression of inflammation-related genes, changes in oxidative stress, and cell proliferation and migration) and evaluated the effect of BPA exposure on inflammation-related markers in epidemiologic studies using repeat urine and serum samples from elderly subjects. BPA induced COX-2 expression via nuclear translocation of NF-κB and activation of mitogen-activated protein kinase (MAPK) by phosphorylation of ERK1/2 and enhanced the migration of lung cancer A549 and breast cancer MDAMB-231 cells. In two epidemiologic studies, we detected associations of BPA with six inflammation-related markers (WBC, CRP, IL-10, ALT, AST, and γ-GTP levels). Our findings probably suggest that BPA exposure induces inflammation and exacerbates tumorigenesis. •BPA induces COX-2 expression in lung cancer A549 and breast cancer MDAMB-231 cells.•Induction of COX-2 is through nuclear translocation of NF-κB and activation of MAPK.•BPA enhances the migration of A549 and MDAMB-231 cells.•Relations between BPA and inflammation-related markers were evaluated in elderly.•BPA exposure was associated with WBC, CRP, IL-10, ALT, AST, and γ-GTP levels.